Essays in Development and Gender Economics - Frezza, Eugenia Maria (Trinity College Dublin. School of Social Sciences & Philosophy. Discipline of Economics, 2024)
This thesis consists of three essays at the intersection of development and gender economics. Each chapter addresses significant questions that aim to understand the origins of harmful practices and norms that impact girls and women. The thesis mainly employs empirical methods within a causal inference framework. Chapter 1 studies the high tolerance towards intimate partner violence (IPV) in a setting where women have limited outside options. It tests whether tolerance of violence acts as a coping mechanism for IPV victims and survivors and how this mechanism may differ in short-term and long-term exposure to abuse. First, it theoretically shows that in settings where exiting a marriage is very costly, it becomes optimal for victims and survivors to increase their tolerance towards IPV as a coping mechanism, but only after prolonged exposure to violence. It tests this hypothesis in the context of India, using a Regression-Discontinuity-Design and an Event Study approach to study the causal link between IPV and tolerance thereof in the short and long term. The context of this study is India. High rates of IPV and alcohol-related abuse characterise India, and its acceptance is also widespread. To uncover the causal effect of experiencing violence on attitudes, it exploits the variation in the legal drinking age within and across Indian states. There are three main takeaways from this study. First, the attainment of the legal drinking age by husbands significantly increases their wives’ probability of being abused by 4-5 percentage points. Second, a rise in the prevalence of domestic violence in the short term does not lead to a shift in the victims’ attitudes toward violence. Instead, the length of exposure to abuse is a crucial factor. Third, evidence indicates that long-term exposure to violence shifts women’s attitudes towards violence by up to 0.3 standard deviations. This suggests that over time, victims may normalise and rationalise the violence inflicted on them as a coping mechanism if they do not have an outside option. Chapter 2 studies whether the internet is a tool for women’s empowerment or whether it exacerbates discriminatory gender norms. It answers this question by exploiting the gradual arrival of fast internet between 2008-2012 on African coasts via submarine cables from Europe. In doing so, the causal effect of the internet on gender norms around attitudes towards intimate partner violence (IPV) is retrieved. Specifically, employing a difference-in-differences strategy, this study compares individuals’ attitudes towards violence in locations with high internet penetration and those without, exploiting differences in the timing of the high-speed internet arrival. Results show that fast internet leads to more regressive gender norms, especially among men. It then explores the potential mechanisms behind this result. The most likely channel in this setting operates via the internet changing the balance of power within the household by affecting labour market opportunities more for men than for women. Chapter 3 assesses whether a law prohibiting and criminalising child marriage is an effective tool to curtail this practice. We extend our analysis to investigate whether the policy has unintended consequences on other harmful practices. Specifically, we study whether policies increasing the cost of child marriage might generate an unintended increase in female genital cutting (FGC). To this end, it employs survey data and it exploits the staggered adoption of laws banning child marriages across Nigerian states between 2003-2022. The findings show that, while these policies were effective in reducing child marriage, they had unintended consequences and increased the prevalence of female genital cutting. The results suggest that child marriage and FGC are substitute traits in the marriage market.
APPROVED
Keywords: Development Economics; Gender Economics; Violence against women and girls; Social norms